Small-molecule-based inhibition of histone demethylation in cells assessed by quantitative mass spectrometry. - Mackeen, M; Kramer, H; Chang, K; Coleman, M; Hopkinson, R; Schofield, C; Kessler, B (2010)
Post-translational modifications on histones are an important mechanism for the regulation of gene expression and are involved in all aspects of cell growth and differentiation, as well as pathological processes including neurodegeneration, autoimmunity, and cancer. A major challenge within the chromatin field is to develop methods for the quantitative analysis of histone modifications. Here we report a mass spectrometry (MS) approach based on ultraperformance liquid chromatography high/low collision switching (UPLC-MS(E)) to monitor histone modifications in cells. This approach is exemplified by the analysis of trimethylated lysine-9 levels in histone H3, following a simple chemical derivatization procedure with d(6)-acetic anhydride. This method was used to study the inhibition of histone demethylases with pyridine-2,4-dicarboxylic acid (PDCA) derivatives in cells. Our results show that the PDCA-dimethyl ester inhibits JMJD2A catalyzed demethylation of lysine-9 on histone H3 in human HEK 293T cells. Demethylase inhibition, as observed by MS analyses, was supported by immunoblotting with modification-specific antibodies. The results demonstrate that PDCA derived small molecules are cell permeable demethylase inhibitors and reveal that quantitative MS is a useful tool for measuring post-translational histone modifications in cells.